Pengaruh Kepemilikan Institusional, Transfer Pricing, dan Sales Growth terhadap Tax Avoidance - Nindiana Okta Auliya; Juli Ratnawati; Enny Susilowati Mardjono; Ratna Herawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research uses a quantitative approach aimed at determining the influence of institutional ownership, transfer pricing, and sales growth on tax avoidance in energy companies listed on the Indonesia Stock Exchange in 2019-2022. The population in this research is all energy companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used purposive sampling technique which resulted in a total sample of 14 companies and a total of 56 data. The analysis technique uses multiple linear regression analysis. The research results conclude that institutional ownership has a negative effect on tax avoidance. Meanwhile, transfer pricing and sales growth have no influence on tax avoidance.